Clinical diagnostic criteria for IgG4‐related sclerosing cholangitis 2020: (Revision of the clinical diagnostic criteria for IgG4‐related sclerosing cholangitis 2012). (26th February 2021) - Nakazawa, Takahiro; Kamisawa, Terumi; Okazaki, Kazuichi; Kawa, Shigeyuki; Tazuma, Susumu; Nishino, Takayoshi; Inoue, Dai; Naitoh, Itaru; Watanabe, Takayuki; Notohara, Kenji; Kubota, Kensuke; Ohara, Hirotaka; et al.
Abstract: Several years have passed since the clinical diagnostic criteria for IgG4‐related sclerosing cholangitis 2012 were published. New findings and knowledge have accumulated since then. The Research Committees for IgG4‐related Diseases and for Intractable Diseases of the Liver and Biliary Tract, in association with the Ministry of Health, Labor, and Welfare of Japan and the Japan Biliary Association, have established a working group consisting of researchers specializing in IgG4‐SC and have drawn up new clinical diagnostic criteria for IgG4‐SC 2020. The diagnosis of IgG4‐SC is based on a combination of the following six criteria: (a) narrowing of the intra‐ or extrahepatic bile duct; (b) thickening of the bile duct wall; (c) serological findings; (d) pathological findings; (e) other organ involvement; and (f) effectiveness of steroid therapy. These new diagnostic criteria for IgG4‐SC are useful in practice for general physicians and other non‐specialists. Abstract : The Research Committees for IgG4‐related Diseases and for Intractable Diseases of the Liver and Biliary Tract in association with the Ministry of Health, Labour and Welfare of Japan and the Japan Biliary Association created the Clinical Diagnostic Criteria for IgG4‐related Sclerosing Cholangitis 2020 as a revision of the 2012 version.